2012
DOI: 10.1136/annrheumdis-2011-200937
|View full text |Cite
|
Sign up to set email alerts
|

Belimumab in the treatment of systemic lupus erythematosus: high disease activity predictors of response

Abstract: ObjectivesTo identify factors that predict response to belimumab treatment in the phase 3 BLISS trials of autoantibody-positive systemic lupus erythematosus (SLE) and further analyse clinical efficacy in various patient subsets.MethodsThe BLISS trials compared belimumab 1 and 10 mg/kg versus placebo, all plus standard SLE therapy, over 52 or 76 weeks. Pooled subgroup analyses of week 52 SLE responder index rates (the primary endpoint in both trials) were performed based on demographic characteristics and basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
220
6
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(273 citation statements)
references
References 18 publications
(14 reference statements)
29
220
6
13
Order By: Relevance
“…BAFF-transgenic mouse studies demonstrated that overexpression of BAFF results in development of SLE-like autoimmune pathology including increased autoantibody production (46)(47)(48). Belimumab (Benlysta), a specific inhibitor of BAFF, shows significant efficacy in evidence-based clinical trials for SLE, further supporting the role of BAFF in SLE pathology (49)(50)(51)(52)(53)(54).…”
mentioning
confidence: 98%
“…BAFF-transgenic mouse studies demonstrated that overexpression of BAFF results in development of SLE-like autoimmune pathology including increased autoantibody production (46)(47)(48). Belimumab (Benlysta), a specific inhibitor of BAFF, shows significant efficacy in evidence-based clinical trials for SLE, further supporting the role of BAFF in SLE pathology (49)(50)(51)(52)(53)(54).…”
mentioning
confidence: 98%
“…An exploratory analysis of patients with higher disease activity at baseline suggested lower response rates with placebo plus SOC in these sicker patients (11), as is suggested by the data reported here. Several analyses have confirmed that subsets of SLE patients, definable by serology, race, or disease activity as likely to be more ill and have less response to SOC even in aggressively treated placebo groups (8,9,(12)(13)(14). Additional data suggest that less aggressive background treatments can lower response rates in moderately ill SLE patients (7-9, 15, 16), leaving room to determine whether a targeted treatment with potential ceiling response rate of 40%-50% may be effective.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, to show a statistically significant reduction in severe flare rates with belimumab, the size of the study had to be extended. Pooled analysis of both BLISS trials suggested that belimumab may be particularly effective in patients with higher disease activity at baseline (characterized by a SELENA-SLEDAI ≥ 10, anti-dsDNA positivity or hypocomplementemia), or in patients requiring treatment with corticosteroids [33]. These findings may further help define the profile of patients with enhanced potential to response to a given biological therapy in clinical practice or future trials.…”
Section: Target Populationmentioning
confidence: 92%
“…To this end, suitable patients should be considered to be those who are seropositive and with at least moderate disease severity (SLEDAI > 6) despite receiving optimal treatment [33]. Such patients with smoldering disease are not uncommon in clinical practice and, more importantly, they tend to accumulate damage over time.…”
Section: Who Should We Treat With Belimumab?mentioning
confidence: 99%